Studi Pengembangan Rute Penerbangan Terintegrasi Di Indonesia - Tri Sefrus (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Air passenger demand in Indonesia has continued to increase since the last decade. According to IATA Indonesia will become the world’s six largest airline travel market by 2034. One of the impacts that is currently felt is the high flight delay. The efforts that have been carried out so far in anticipation of increasing the number of passengers and airport overcapacity are through the development of existing airports; both terminal expansion and runway upgrades. In fact, physical development can not be carried out continuous airport development alternative through integrated flight routes.